Evaluation of Monomer Releasing from Dentin Replacement Materials - Nurgül Çetin Tuncer; Sevde Gül Batmaz; Sergen Özdemir; Çağatay Barutçugil; Ayşe Dündar; Kardelen Yıldırım (International Journal of Polymer Science)
The aim of this study is to determine and quantify the monomer elution from four different resin-based composite dentin replacement materials for 3 months using HPLC. Four different composite dentin replacement materials were used in the present study: EverX (EVX), X-tra base (XTB), SDR (SDR), and GrandioSO Heavy Flow (GHF). Fifteen samples from each material were prepared (5×5×4 mm). After preparation, each specimen was immersed in a 10 ml 75% ethanol/distilled water solution for three different periods: 1 h, 24 h, and 3 months (n=5). After the immersion period, 0.5 ml of solutions were taken from each bottle and analyzed using HPLC. At the end of the 3-month immersion period, the elution of monomers was determined mostly from SDR, GHF, EVX, and XTB, respectively. TEGDMA, the most released monomer of all groups, was released from all samples after 1 h, 24 h, and 3 months. The amount of monomer released in all composite groups at the end of the 3-month immersion period was significantly higher than the monomer amounts released after the 1-hour immersion period. The monomers were eluted from the composite dentin replacement materials during all immersion periods, and the amount of eluted monomers was increased with time.